2016
DOI: 10.1088/1538-3873/128/960/024402
|View full text |Cite
|
Sign up to set email alerts
|

Exoplanet Transits Registered at the Universidad de Monterrey Observatory. I. HAT-P-12b, HAT-P-13b, HAT-P-16b, HAT-P-23b, and WASP-10b

Abstract: Forty transits of the exoplanets HAT-P-12b, HAT-P-13b, HAT-P-16b, HAT-P-23b and WASP-10b were recorded with the 0.36m telescope at the Universidad de Monterrey Observatory. The images were captured with a standard Johnson-Cousins Rc and Ic and Sloan z' filters and processed to obtain individual light curves of the events. These light curves were successfully combined for each system to obtain a resulting one of higher quality, but with a slightly larger time sampling rate. A reduction by a factor of about four… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 38 publications
2
16
1
Order By: Relevance
“…Spectroscopic and photometric studies have confirmed and improved upon the discovery values (Husnoo et al 2012;Ciceri et al 2013;Pearson et al 2014;Sada & Ramón-Fox 2016). It was found through Rossiter-McLaughlin observations (Moutou et al 2011) that HAT-P-16b's projected spin-orbit angle of λ = −10 • ± 16 • is aligned with the stellar spin axis.…”
Section: Hat-p-16bmentioning
confidence: 78%
See 1 more Smart Citation
“…Spectroscopic and photometric studies have confirmed and improved upon the discovery values (Husnoo et al 2012;Ciceri et al 2013;Pearson et al 2014;Sada & Ramón-Fox 2016). It was found through Rossiter-McLaughlin observations (Moutou et al 2011) that HAT-P-16b's projected spin-orbit angle of λ = −10 • ± 16 • is aligned with the stellar spin axis.…”
Section: Hat-p-16bmentioning
confidence: 78%
“…Follow-up photometry studies have refined the planetary parameters of HAT-P-13b and searched for possible transit timing variations (Szabó et al 2010;Winn et al 2010;Fulton et al 2011;Pál et al 2011;Nascimbeni et al 2011;Southworth et al 2012a;Sada & Ramón-Fox 2016). In addition, Winn et al (2010) performed Rossiter-McLaughlin effect measurements of the system and found that HAT-P-13b is likely aligned (1.…”
Section: Hat-p-13bmentioning
confidence: 99%
“…Timing residuals for HAT-P-23 b. White points are data obtained and reanalyzed byMaciejewski et al (2018) and originally reported byBakos et al (2011);Ramón-Fox & Sada (2013);Ciceri et al (2015) andSada & Ramón-Fox (2016). Black points represent new data.…”
mentioning
confidence: 90%
“…HIP 14810 b). For the transiting planets, we adopted the photometrically derived orbital periods for HAT-P-1 b (Johnson et al 2008), HAT-P-3 b (Chan et al 2011), HAT-P-12 b (Sada & Ramón-Fox 2016), HD 149026 b (Carter et al 2009), and XO-5 b (Smith 2015). For HAT-P-4 b and HD 17156 b, the radial velocities alone were sufficient to determine the orbital periods without any significant loss in precision.…”
Section: One Planet For Hd 207832 Instead Of Twomentioning
confidence: 99%